2023
DOI: 10.1289/ehp11580
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Analysis of Lung Lymph Nodes in a Mouse Model of Allergic Lung Inflammation following PM2.5 and Indeno[1,2,3- cd ]pyrene Exposure

Abstract: Background: Ambient particulate matter with an aerodynamic diameter of ( ) is suggested to act as an adjuvant for allergen-mediated sensitization and recent evidence suggests the importance of T follicular helper (Tfh) cells in allergic diseases. However, the impact of exposure and its absorbed polycyclic aromatic hydrocarbon (PAHs) on Tfh cells and humoral immunity remains unknown. Objectives: We aimed to explore the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…provide a detailed characterization of immune effects of fine particulate matter [PM with an aerodynamic diameter of ( )] obtained from atmospheric monitoring stations in Taiwan. 3 This contained various polycyclic aromatic hydrocarbons (PAHs), including indeno[1,2,3- cd ]pyrene (IP). 4 They observed that intratracheal administration of or IP alone exacerbated pathology and modulated immune responses by using a mouse model for house dust mite (HDM)-mediated asthma.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…provide a detailed characterization of immune effects of fine particulate matter [PM with an aerodynamic diameter of ( )] obtained from atmospheric monitoring stations in Taiwan. 3 This contained various polycyclic aromatic hydrocarbons (PAHs), including indeno[1,2,3- cd ]pyrene (IP). 4 They observed that intratracheal administration of or IP alone exacerbated pathology and modulated immune responses by using a mouse model for house dust mite (HDM)-mediated asthma.…”
mentioning
confidence: 99%
“… 4 They observed that intratracheal administration of or IP alone exacerbated pathology and modulated immune responses by using a mouse model for house dust mite (HDM)-mediated asthma. 3 Importantly, they used mass cytometry to determine that both and IP exposure increased the percentage and number of T follicular helper (Tfh) cells in the lung-draining lymph nodes. In addition, the enhancement in Tfh cells was dependent on AHR expression in T cells, at least for .…”
mentioning
confidence: 99%
See 3 more Smart Citations